2012
DOI: 10.1128/aem.07457-11
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Mannan Binding Family 32 Carbohydrate Binding Module on the Activity of the Appended Mannanase

Abstract: eIn general, cellulases and hemicellulases are modular enzymes in which the catalytic domain is appended to one or more noncatalytic carbohydrate binding modules (CBMs). CBMs, by concentrating the parental enzyme at their target polysaccharide, increase the capacity of the catalytic module to bind the substrate, leading to a potentiation in catalysis. Clostridium thermocellum hypothetical protein Cthe_0821, defined here as C. thermocellum Man5A, is a modular protein comprising an N-terminal signal peptide, a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
24
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 22 publications
12
24
0
1
Order By: Relevance
“…Specificity to LacNAc (␤-D-galactosyl-1,4-␤-D-N-acetylglucosamine) was also shown for a CBM32 of N-acetylhexosaminidase from C. perfringens (16). More recently, a mannan binding module belonging to the CBM32 family was found in a ␤-1,4-mannanase from Clostridium thermocellum (38). In this study thermal unfolding experiments suggested that DD1 in a chitosanase from Paenibacillus sp.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Specificity to LacNAc (␤-D-galactosyl-1,4-␤-D-N-acetylglucosamine) was also shown for a CBM32 of N-acetylhexosaminidase from C. perfringens (16). More recently, a mannan binding module belonging to the CBM32 family was found in a ␤-1,4-mannanase from Clostridium thermocellum (38). In this study thermal unfolding experiments suggested that DD1 in a chitosanase from Paenibacillus sp.…”
Section: Discussionsupporting
confidence: 59%
“…Binding Affinities of (GlcN) n -A recent study on a mannan binding module belonging to CBM32 revealed a greater contribution of the entropic penalty to interactions with ␤-1,4-mannno-oligosaccharides (ϪT⌬S r°ϭ about 5.0 kcal/mol) (38). This situation resulted in less favorable free energy changes in the interactions (⌬G r°ϭ Ϫ5.5 kcal/mol) than those obtained for (GlcN) n (n Ն 2) interactions with DD1 (⌬G r°ϭ Ϫ7.0 ϳ Ϫ8.0 kcal/mol).…”
Section: Discussionmentioning
confidence: 99%
“…Mannotriose accesses the binding sites on CtCBM35 more easily than a galactose substituted branched polysaccharide like locust bean galactomannan. This was similarly reported earlier by Mizutani et al [25]. However, no significant binding of CtCBM35 was observed with carboxymethyl cellulose, rye arabinoxylan, birchwood xylan, oat spelt xylan, and glucuronoxylan, showing that CtCBM35 is mannan specific CBM ( Table 1).…”
Section: Resultssupporting
confidence: 89%
“…This suggested that CtCBM35 bound less significantly with insoluble ivory nut mannan. The low affinity against insoluble mannan has been reported for the inability of "trans" form (as a separate fold and not appended to a hydrolytic enzyme) of CBM to disrupt the interchain interactions of the poly saccharide [25]. This is in contrast to some CBMs that have the ability to disintegrate the surface of crystalline insoluble polysaccharides displaying higher binding to soluble fractions of insoluble polysaccharides [27,28].…”
Section: Resultsmentioning
confidence: 99%
“…Unlike typical oligosaccharide-specific solute-binding proteins, CpMnBP1 engages mannan sugars through the nonreducing end. Although unexpected, such a binding mode is not without precedent as the family 32 carbohydrate-binding module from Clostridium thermocellum has been demonstrated to similarly engage manno-oligosaccharides through the non-reducing end (37). Likewise, structural studies of the family 6 carbohydrate-binding module reveal that ␤-1,3-glucan chains are targeted through the non-reducing end of the saccharide (38).…”
Section: Discussionmentioning
confidence: 99%